(untitled) (Raparin Journal of Humanities (RJH), 2026)
The rule of the Median country is considered as one of the periods in the history of ancient east, because in many ways which had a great influence on the civilization and countries after it. The Median nation by came to heights of Iran and after settling on this land, the water and air of the region were suitable for settlement. They developed their own external political system, which was expansionism and liberation from Assyrian dominion. Diako founded this political system and it reached its peak of development under Kiaksar. Eventually, it was the Medes who, in agreement with the ability of their neighbors such as Babylon, removed of the Assyrians from the political field. A number of Median commanders at the beginning of the govern of Cyrus II and Astyages the last Median kings advantaged from the help of Cyrus the Persian and In this regard, they played a major role in the devastation of the Median nation and the rise of the Achaemenid nation. Despite all that has been done, the Political history external the media is one of the most complicated topics in the political history of the Old East and still remains very unclear. Although, it has not been completely studied, this paper discusses the most significant political changes external of the Median nation, with nation such as Assyria, Orthodoxy, Scythians, Babylon, etc., which is more objectively based on the method (description-analysis) and comparative interpretation of changes and events.